What Makes a Street Attractive? A Study of The Factors Explaining the Attractiveness of Users of Two Streets in Algiers Using Linear Regressions - Kadri, Ouafa; Rahmani, Lyes; Messaoudene, Maha (Indonesian Journal of Social Science Research, 2024)
This article examines the factors behind attractiveness at street level. It postulates that attractiveness is induced by what the street offers in terms of consumption spaces and by the presence of convenience. The study focused on two streets in Algiers: one historical entity and one emerging entity. A sample of 269 individuals was used to collect data using a tool that measures attractiveness, convenience, and consumption spaces. These include commercial, cultural, leisure, symbolic, social and landscape dimensions. Linear regressions were used to determine the impact of these dimensions on the attractiveness. The results show that the symbolic dimension, followed by the social dimension, are the factors with the greatest influence on street attractiveness.